THE ASSISTANCE TO WOMEN VICTIMS OF DOMESTIC VIOLENCE: AN ANALYSIS OF VICTIM SERVICES IN TOCANTINS (Editora Impacto Científico, 2025)
The article presents a discussion on domestic violence against women and examines the performance of the Maria da Penha Patrol in Tocantins regarding the effectiveness of emergency protective measures for victims. The general objective of the research is to analyze the performance of the Maria da Penha Patrol in the State of Tocantins for the effectiveness of emergency protective measures. The methodology is qualitative in nature, with an exploratory and analytical approach, based on literature review, document analysis, and secondary data collection. The study identifies domestic violence as a structural and multifactorial phenomenon that requires coordinated responses among the judiciary, public security, social assistance, and health sectors. The results show that the Maria da Penha Patrol strengthens the protection network by allowing victim monitoring, follow-up of judicial measures, and educational prevention actions. However, there remains a need to overcome institutional, cultural, and infrastructure challenges by ensuring continuous officer training and effective integration among agencies. It is concluded that the effectiveness of protective measures requires intersectoral coordination, permanent investments, and public policies sensitive to the victims’ context, highlighting the innovative role of the Maria da Penha Patrol in strengthening women’s citizenship in Tocantins.DOI: https://doi.org/10.56238/edimpacto2025.090-019